Edutok engaging young minds in islamic business transactions through Tiktok - Osman, ‘Ismah; Shaharuddin, Norhasimah; Muhamad Ariffin, Nur Afizah; Khamis, Mohd Rahim; Mohamad Shafi, Roslina; Abdullah, Hasni (2025)
The rise of short-form video platforms has transformed digital content consumption, especially among Generation Z. TikTok, as a leading social media app, is an innovative platform for teaching Fiqh Muamalat, a branch of Islamic law concerning business transactions. This study investigates TikTok’s effectiveness as a learning tool for Fiqh Muamalat and examines students’ attitudes, perceived usefulness, and intention to use it for learning. Using a quantitative approach, data were collected from 126 undergraduate students enrolled in an “Introduction to Fiqh Muamalat” course via a structured questionnaire. Descriptive statistics, t-tests, Pearson correlation, and multiple regression analyses were employed. The findings reveal that students with a prior Islamic studies background held more favorable attitudes toward TikTok. A significant proportion (61.9%) followed TikTok accounts related to Fiqh Muamalat, with many valuing its creative, visually engaging content that reinforces classroom learning. Attitudes and perceived usefulness were strong predictors of students’ intention to use TikTok, explaining 42% of the variance. Institutional endorsement of TikTok content was also associated with increased engagement. While TikTok offers opportunities for active and relatable learning, challenges such as content authenticity and digital literacy remain. This study highlights the platform’s potential as a supplementary educational tool in Islamic legal studies and calls for structured integration with formal curricula to ensure theological accuracy and pedagogical effectiveness.